Devil in the white city murder, magic & madness and the fair that changed America - Larson, Erik; Goldwyn, Tony (New York Random House Audio, 2005)
The drama of the 1893 Chicago World's Fair springs to life through two characters, Architect Daniel Hudson Burnham, the fair's brilliant director of works, and murderer Dr. Henry H. Holmes. While Burnham overcomes extreme personal challenges to build the famed White City, the sinister Holmes, possibly responsible for scores of murders, lures people to his World's Fair Hotel, complete with gas chambers and a crematorium.
Abridged
Subtitle from container
Read by Tony Goldwyn.
Compact discs.
103912
Keywords: Mudgett, Herman W. -- 1861-1896; Serial murderers -- Illinois -- Chicago; Audiobooks; Illinois -- Chicago; Biography; Case studies